Vocation for planetary citizenship: Lutheran liberal arts education in the Anthropocene. Issue 2 (19th June 2018) - Simmons, Ernest L.
Abstract: The focus question of this article is, "In what ways should Lutheran higher education's teaching on vocation be revised to include the fact that we are living in a natural world massively impacted by human behavior, the Anthropocene Era?" This can be broken down into two more explicit questions: "What is the role of liberal arts education in such a changed context?" and "What resources in the Lutheran tradition can contribute to preparing students to become effective sustainability leaders?" The thesis of this article is that Lutheran liberal arts education, to foster planetary citizenship, must move students from an anthropocentric to an ecocentric understanding of vocation, preparing them to become leaders for a sustainable, interfaith society. This change can be accomplished by reaffirming the value of the liberal arts to foster sustainability education and retrieving Luther's understanding of creation to elicit wonder and appreciation of the natural world.